2021
DOI: 10.1155/2021/6611085
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Interleukin-16-Neutralizing Antibody Attenuates Cardiac Inflammation and Protects against Cardiac Injury in Doxorubicin-Treated Mice

Abstract: Background. Interleukin-16 (IL-16) is an important inflammatory regulator and has been shown to have a powerful effect on the regulation of the inflammatory response. Cardiac inflammation has been reported to be closely related to doxorubicin- (DOX-) induced cardiac injury. In this study, the role of IL-16 in DOX-induced cardiac injury and the possible mechanisms were examined. Methods. Cardiac IL-16 levels were first measured in DOX- or saline-treated mice. Additionally, mice were pretreated with the anti-IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…4 Around the time of symptom onset, the case patient also displayed elevated levels of other cytokines, IL-5, IL-16, and MIG (CXCL9), which play inflammatory roles in either myocarditis or related cardiac complications in humans or in experimental animal models. 5–8 In contrast, relative to N M or N UV , the first sample of the case patient (CI S1 ) showed a decrease in the levels of cytokine LIF, which provides cellular stability and ensures survival of cardiomyocytes during stress. 9 The other 3 cytokines, VEGF, IL-10, and MIF, did not reveal a unidirectional regulatory pattern with comparators (N M and N UV ); however, each spiked above the N UV reference group and has been individually implicated in immune vasculitis.…”
Section: Results Of Exploratory Studiesmentioning
confidence: 96%
“…4 Around the time of symptom onset, the case patient also displayed elevated levels of other cytokines, IL-5, IL-16, and MIG (CXCL9), which play inflammatory roles in either myocarditis or related cardiac complications in humans or in experimental animal models. 5–8 In contrast, relative to N M or N UV , the first sample of the case patient (CI S1 ) showed a decrease in the levels of cytokine LIF, which provides cellular stability and ensures survival of cardiomyocytes during stress. 9 The other 3 cytokines, VEGF, IL-10, and MIF, did not reveal a unidirectional regulatory pattern with comparators (N M and N UV ); however, each spiked above the N UV reference group and has been individually implicated in immune vasculitis.…”
Section: Results Of Exploratory Studiesmentioning
confidence: 96%
“…36 Strategies to prevent overt immune activation and inflammatory responses have shown great potentials for treating cardiovascular diseases, including DOX-induced cardiotoxicity. 37,38 The unbiased RNA-seq results in our present study revealed that neutrophil chemotaxis inhibition might be involved in the cardioprotective effects of LIPUS therapy. Further flow cytometry analyses illustrated the inhibitory effect of LIPUS treatment on DOX-induced neutrophil recruitment and infiltration in the heart.…”
Section: Discussionmentioning
confidence: 57%
“…The importance of immunity and inflammatory mechanisms in cardiovascular diseases has drawn more and more attentions 36 . Strategies to prevent overt immune activation and inflammatory responses have shown great potentials for treating cardiovascular diseases, including DOX‐induced cardiotoxicity 37,38 . The unbiased RNA‐seq results in our present study revealed that neutrophil chemotaxis inhibition might be involved in the cardioprotective effects of LIPUS therapy.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, in this respect, IL-16 seems to enhance atherosclerotic development. Overexpression of IL-16 augmented cardiac inflammation, leading to increased cardiac fibrosis, while inhibition of IL-16 by administering an IL-16 neutralizing antibody attenuated doxorubicin-induced cardiac injury 14,16 . However, we observed that IL-16 conferred beneficial effects on vascular lesions in this study, which is consistent with a clinical investigation showing that a high level of IL-16 is positively correlated with a reduced risk for cardiovascular events, 17 suggesting the existence of an alternative mechanism underlying IL-16 function.…”
Section: Discussionmentioning
confidence: 99%
“…14 Neutralizing treatment with an anti-IL16 antibody alleviated cardiac inflammation and fibrosis and improved cardiac dysfunction. [14][15][16] This evidence indicates that IL-16 has an adverse effect on cardiovascular function. However, contrary results show that elevated IL-16 in both circulation and carotid plaques is associated with a reduced incidence of cardiovascular events in patients with advanced atherosclerotic lesions.…”
mentioning
confidence: 93%